Redesain e-Persediaan Berbasis Sistem Informasi Akuntansi pada Pemerintah Provinsi Gorontalo - Suci Rachmawati Yusuf; Mahdalena Mahdalena; Hartati Tuli (Al-Buhuts, 2024)
This study aimed to redesign the accounting information system-based E-Inventory at the Provincial Government of Gorontalo. This study adopted a qualitative approach using descriptive methods. The study involved three informants. The data were collected through observation, interviews, and documentation. The data analysis techniques employed in this study include data reduction, data display, and conclusion/verification. The findings of this study indicated that the E-Inventory system can be represented through Unified Modeling Language (UML) diagrams and flowcharts as the redesign model. The PIECES analysis wa utilized in the redesign process to analyze the weaknesses of the E-Inventory system. Based on this analysis, system failures were identified in the E-Inventory, such as duplicate entries during transaction input and the need for initial inventory balance entry for the subsequent period. Therefore, these recording and input errors can be minimized by redesigning the E-Inventory system. This redesign is undertaken to enchance the efficiency of the E-Inventory system in accordance with the inventory management needs of consumable goods at the Provincial Government of Gorontalo